Nondestructive Method for the Determination of the Electric Polarization Orientation in Thin Films: Illustration on Gallium Ferrite Thin Films. Issue 12 (13th November 2017) - Lefevre, Chistophe; Demchenko, Anna; Bouillet, Corinne; Luysberg, Martina; Devaux, Xavier; Roulland, François; Versini, Gilles; Barre, Sophie; Wakabayashi, Yusuke; Boudet, Nathalie; Leuvrey, Cédric; Acosta, Manuel; et al.
Abstract: The knowledge and control of the electric polarization in multiferroic thin films is currently the subject of extensive research efforts. This is the key toward a possible transformation into devices of the exciting phenomena such as conductance modification or polarity observed at ferroelectric domain walls. The main methods currently available to determine the polarization characteristics in thin films suffer from being local, time demanding, potentially vitiated by artefacts, or even blinded in some cases. A nondestructive method based on resonant diffraction is proposed for the determination of the polarization orientation in multiferroic, ferroelectric, or pyroelectric thin films. The method is experimentally illustrated for multiferroic gallium ferrite thin films. Its validity is also theoretically shown for the perovskite‐based structure of the emblematic ferroelectric Pb(Zr, Ti)O3, which augurs numerous prospects for its potential applications. Abstract : A new method for nondestructive and artefact free determination of the polarization orientation in ferroelectric thin films is introduced. The method, based on resonant diffraction, is experimentally illustrated for multiferroic gallium ferrite thin films. Its validity is also theoretically shown for the perovskite‐based structure of the emblematic ferroelectric PZT. This augurs considerable perspectives for the potential applications of the method.